Reminiscing to teach others and prepare for death is associated with meaning in life through generative behavior in elderlies from four cultures. (3rd May 2020) - Hofer, Jan; Busch, Holger; Au, Alma; Poláčková Šolcová, Iva; Tavel, Peter; Tsien Wong, Teresa
Abstract: Objectives : Reminiscence is considered an important aspect of successful ageing. Prominent reminiscence functions in old age are to pass on important experiences (Teach/Inform) and to prepare for death (Death Preparation). These reminiscence functions were hypothesized to be associated with generative behavior which in turn was hypothesized to be associated with meaning in life. Thus, we tested an indirect effect of reminiscence functions on meaning in life mediated by generative behavior. Method : Elderly participants provided information on reminiscence functions, generative behavior, and meaning in life. Participants were recruited in Cameroon, China (Hong Kong), the Czech Republic, and Germany, to test the generalizability of findings. Results : The assumed indirect effect was identified: Reminiscence functions were associated with meaning in life via generative behavior. This pattern was found for all cultural samples. Conclusion : Albeit results have to be interpreted with caution as they are based on cross-sectional data, findings suggest that these reminiscence functions motivate generative behavior and thus indirectly affect meaning in life in elderlies from all four cultural contexts. In future studies, this effect needs to be replicated with a broader age range and a more fine-grained measure of generative behavior to account for potential differences in culturally appropriate generative outlets.